Reverberation Mapping Data of NGC 5548 Imply a Multicomponent Broad-line Region - Kirk Long; Jason Dexter (The Astrophysical Journal, 2025)
Line broadening and variability are observational hallmarks of active galactic nuclei (AGN) which allow us to measure supermassive black hole masses as well as constrain the geometry and kinematics of the emitting gas, with the most precise measurements requiring a degree of modeling. Two popular models of the broad-line region (BLR) describe the emitting gas as either a distribution of puffed-up clouds or a thin disk with strong velocity gradients. As we show in this work, key features in the reverberation mapping data set obtained by the AGN-STORM team in NGC 5548 cannot be accounted for by either simple model. In several emission lines the observed broad-line profile has a single peak yet the delay profile has a distinct double peak, strongly motivating a BLR with emission from multiple components. We demonstrate a few possibilities that may alleviate the tension and better represent the true nature of the broad-line-emitting gas in NGC 5548 and beyond.